2019
DOI: 10.15252/embj.2019101997
|View full text |Cite
|
Sign up to set email alerts
|

Microglial subtypes: diversity within the microglial community

Abstract: Microglia are brain‐resident macrophages forming the first active immune barrier in the central nervous system. They fulfill multiple functions across development and adulthood and under disease conditions. Current understanding revolves around microglia acquiring distinct phenotypes upon exposure to extrinsic cues in their environment. However, emerging evidence suggests that microglia display differences in their functions that are not exclusively driven by their milieu, rather by the unique properties these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
370
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(390 citation statements)
references
References 154 publications
(272 reference statements)
17
370
0
3
Order By: Relevance
“…The expression data showed that several genes from the category "regulation of MAPK cascade" were differentially regulated in both Csf1-/-and wild type mice ( Figure 5B,C). Many of the genes within this category (Apoe, Csf1R, Ccl7, Ccl2, Tlr6, Tlr13, Ccl9, Ccl3, and Clec7a) are known to be developmentally and/or pathologically-regulated in microglia [54][55][56][57] and, as expected, were significantly less upregulated after demyelination in Csf1-/-than in wild types. Interestingly, within this category, we identified a group of genes significantly upregulated (p < 0.05) in Csf1-/-mice.…”
Section: Reduction Of Microglia/macrophages Alters Pan-glia Responsesupporting
confidence: 69%
“…The expression data showed that several genes from the category "regulation of MAPK cascade" were differentially regulated in both Csf1-/-and wild type mice ( Figure 5B,C). Many of the genes within this category (Apoe, Csf1R, Ccl7, Ccl2, Tlr6, Tlr13, Ccl9, Ccl3, and Clec7a) are known to be developmentally and/or pathologically-regulated in microglia [54][55][56][57] and, as expected, were significantly less upregulated after demyelination in Csf1-/-than in wild types. Interestingly, within this category, we identified a group of genes significantly upregulated (p < 0.05) in Csf1-/-mice.…”
Section: Reduction Of Microglia/macrophages Alters Pan-glia Responsesupporting
confidence: 69%
“…Recently, deep single-cell RNA sequencing (scRNAseq) data from isolated microglia cells has revealed several transcriptionally distinct clusters throughout each developmental stage [170][171][172]. Based on this evidence, Stratoulias and colleagues (2019) hypothesized that microglia constitute a heterogeneous population, in which each cell displays intrinsic properties and functional specializations regardless of the structure [173]. As a result, neighboring microglial cells may have different responses to the same stimulus.…”
Section: Perspectivesmentioning
confidence: 99%
“…Moreover, so-called M1 and M2 gene signatures often coexist in complex mixed phenotypes; the dichotomous paradigm is not supported by transcriptional profiling of human macrophages or monocytes activated by diverse ligands (22). Emerging evidence suggests that microglial subtype categorization should consider both their environmentdependent plasticity and subtypes with inherent functional specificity (23). Technologies that can assist in these efforts include two-photon imaging, whole-genome transcriptomic and epigenomic analyses at the cellular level, mass cytometry, and high-content experimental models (19).…”
Section: Measuring Inflammation In the Brain And Periphery: Beyond Pomentioning
confidence: 99%